Optimization and immobilization of amylase produced by Aspergillus terreus using pomegranate peel waste - Ahmed, Nehad E. (2021)
Marine fungal isolate was recovered from red sea water at Sharm El-Sheikh Province and was tested for amylase activity using different agricultural wastes as substrate. It was found that pomegranate peel was the best substrate for amylase production (339 U/ml). Thus, it was subjected for identifying by 18S rDNA gene. The phylogenetic analysis results indicated that this fungal isolate belonged to Aspergillus species with similarity of 99% and named as Aspergillus terrus SS_RS-NE. Its nucleotide sequences were deposited in NCBI GenBank under accession no. of MN901491. Some parameters affecting amylase activity using pomegranate peel as substrate were studied. The results denoted that, the highest amylase activity of 340.69 U/ml using 1.5% pomegranate peel at 30 °C, pH 6.0 on 5 days incubation time by Aspergillus terreus. The produced crude enzyme was partially purified with 80% ammonium sulfate followed by dialysis. The enzyme activity was 1246 U/ml and 2411 U/ml employing ammonium sulfate precipitation and dialysis respectively.